Evaluasi Program Desaku Menanti dalam Penanggulangan Gelandangan dan Pengemis di Kota Padang - Vania Cynthia; Rahmadani Yusran (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2021)
This study aims to analyze the evaluation of the Desaku Menanti Program in dealing with homeless people and beggars in the city of Padang. The basis for the implementation of the my village program is regulated in the Padang City Regional Regulation Number 1 of 2012 concerning Development of Street Children, Homeless People, Beggars, Singers and Street Vendors. The objectives of the village waiting program are 1) Improving people's ability to carry out their social functions properly in society. 2) Improve the ability of people and the social environment to solve social problems. 3) Improving people's social status and roles so that they can adapt to their environment. This program is an innovation of the programs for handling the homeless, beggars and street children that have been carried out, namely by focusing all services in the areas of origin of homeless people and beggars (village based). This research is a qualitative research using descriptive method. The research informants were determined by purposive sampling. Data collection techniques are carried out by conducting interviews, observations, and documentation studies and data reduction is carried out so that accurate conclusions can be drawn from the data that has been obtained. The results showed that the impact of the implementation of the Desaku Menanti program in dealing with homeless people and beggars in the city of Padang was not optimal. This is because the objectives of the Desaku Menanti program have not been achieved.